Growing into pumpkin custodians: Women farmers in North Vietnam discover the power of participatory variety selection - Nguyen, Thi Phuong; Hoang, Ky The; Do, Thi Hong Quyen; Nabuuma, Deborah; Vernooy, Ronnie (2024)
Blog on participatory variety evaluation of different pumpkin varieties by with two Diet Health Clubs in Northern Vietnam. In the northern highlands of Vietnam, ethnic minority farmers grow a diversity of crops on small landholdings. Pumpkin, managed by women, is an important vegetable in this crop mixture, but the number of varieties is declining. Members of two local Diet Health Clubs engaged in participatory variety evaluation.